2016
DOI: 10.1111/1467-9604.12138
|View full text |Cite
|
Sign up to set email alerts
|

Change management and the SENCo role: developing key performance indicators in the strategic development of inclusivity

Abstract: This article follows an earlier publication highlighting the changing role of special educational needs co-ordinators (SENCos) in England. SENCos are now required to manage change strategically and deliver inclusive school cultures. School-based action research undertaken by a teacher studying for the postgraduate National Award for SEN Co-ordination (NASENCO) is featured in the article; a strategic review of resource allocation increased the availability and quality of interventions for students with special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Whilst Smith and Broomhead (2019) have suggested that there should be locally or nationally agreed policy regarding SLT membership for SENCOs, a pragmatic approach would be to accept that the seniority of the role is mixed and to ensure that both approaches are supported. When the SENCO is not part of SLT, Done, Murphy and Watt (2016) would argue that the SENCO needs to understand the process and landscape of senior management, which further highlights the importance of focusing on leadership within the NA SENCO. Equally, attention needs to be given to the way in which the SENCO, and SEN, is understood and integrated within school structures and systems (Ekins, 2012).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Whilst Smith and Broomhead (2019) have suggested that there should be locally or nationally agreed policy regarding SLT membership for SENCOs, a pragmatic approach would be to accept that the seniority of the role is mixed and to ensure that both approaches are supported. When the SENCO is not part of SLT, Done, Murphy and Watt (2016) would argue that the SENCO needs to understand the process and landscape of senior management, which further highlights the importance of focusing on leadership within the NA SENCO. Equally, attention needs to be given to the way in which the SENCO, and SEN, is understood and integrated within school structures and systems (Ekins, 2012).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The main issue emerging from the findings related to how the position of SENCo was actually a conflict of interest with a SMT role. SENCo 7 (above) illustrated clearly the disconnect and conflict between strategic school development and promoting inclusive practice that Norwich (2010) and Done et al (2016) postulate. While inclusion on SMT for SENCos can be considered a step forward, there are indeed limitations attached to such status for SENCos and therefore should be considered with caution.…”
Section: Sencomentioning
confidence: 97%
“…However, where SENCos are indeed included on SMT, it fails to be a golden situation due to disconnect, conflict and ambiguity of promoting inclusive provision alongside strategic development across schools (Norwich, ; Done et al , ). Furthermore, some SENCos have indicated a desire not to be on SMT, as they consider their contribution of influencing an inclusive culture within their school to be sufficient alongside legal jurisdiction (Maher and Vickerman, ).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of pre‐CoP, 2015 research explored the dual foci of the leadership role of the SENCO as they are expected both to manage the day‐to‐day operational aspects of the role and to lead strategically (Rosen‐Webb, ; Oldham and Radford, ; Done et al , ). Qureshi () would assert that SENCOs are increasingly deemed ‘agents of change’ but states this is dependent on two points: whether they are in the Senior Leadership Team (SLT) and if they are given sufficient time to work as strategic leaders.…”
Section: Recent Literature On the Senco As ‘Change Agent’mentioning
confidence: 99%